Skinput: Appropriating the Skin as an Interactive Canvas - Harrison, Chris; Tan, Desney; Morris, Dan (Communications of the ACM, 2011)
Skinput is a technology that appropriates the skin as an input surface by analyzing mechanical vibrations that propagate through the body. Specifically, we resolve the location of finger taps on the arm and hand using a novel sensor array, worn as an armband. This approach provides an onbody finger input system that is always available, naturally portable, and minimally invasive. When coupled with a pico-projector, a fully interactive graphical interface can be rendered directly on the body. To view video of Skinput, visit http://cacm.acm.org.